Comparison of accelerated and enzyme-associated real-time degradation of HMW PLLA and HMW P3HB films - Daniela Arbeiter; Kerstin Lebahn; Thomas Reske; Volkmar Senz; Thomas Eickner; Klaus-Peter Schmitz; Niels Grabow; Stefan Oschatz (Polymer Testing, 2022)
Designing laboratory-scale degradation experiments for polymer-based biomaterials is crucial for the development of safe and functional implants, in particular regarding high molecular weight polyesters. Within this work, we compared accelerated degradation of solvent cast HMW-PLLA and HMW-P3HB films at 55 °C (16 weeks) with enzyme-associated (proteinase K and lipases) real-time degradation at 37 °C (108 weeks). During real-time degradation, PLLA showed mass loss up to 83%, in contrast to accelerated conditions, where no changes occurred. Moreover, we observed wave-shape development of crystallinity for PLLA and PHB for both degradation conditions applied, whereby PLLA χ value nearly doubled to up to 75%. These results were used to develop a correlation model based on molecular weight decrease and were furthermore discussed in light of a detailed literature review. In summary, real-time in vitro studies could be adapted to accelerated protocols providing the same limiting conditions such as molecular weight and initial crystallinity are given.